Characterization and Prediction of Early Reading Abilities in Children on the Autism Spectrum - Davidson, Meghan M. (2014)
Many children with autism spectrum disorder (ASD) have reading profiles characterized by higher decoding skills and lower reading comprehension. This study assessed whether this profile was apparent in young children with ASD and examined concurrent and longitudinal predictors of early reading. A discrepant profile of reading (higher alphabet and lower meaning) was found in 62% of this sample. Concurrent analyses revealed that reading proficiency was associated with higher nonverbal cognition and expressive language, and that social ability was negatively related to alphabet knowledge. Nonverbal cognition and expressive language at mean age 2½ years predicted later reading performance at mean age 5½ years. These results support the importance of early language skills as a foundation for reading in children with ASD.